The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1142/s1084946714500095
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Luxury Brand Consumption and Female Consumers' Religiosity in the Uae

Abstract: Luxury brand consumption by female consumers in the rich Arab Gulf states has never been systematically studied, and thus most of our knowledge in this area remains shaped by preconceived notions that are not likely to withstand scientific scrutiny. This study fills that gap in research and provides significant evidence on the actual consumption behavior of this enigmatic consumer segment. In our study, focus groups and expert feedback were used to construct a Luxury Consumption Scale (LCS) to measure actual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 15 publications
3
25
1
1
Order By: Relevance
“…Studies indicated that consumers have different materialistic values and as previously mentioned, several studies have found that religion does not produce negative effects on luxury consumption (Alserhan et al, ; Arli et al, ). In contrast, other studies confirmed that religion has significant effects on luxury consumption (Al‐Hyari et al, ; Burroughs & Rindfleisch, ).…”
Section: Hypothesis Developmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Studies indicated that consumers have different materialistic values and as previously mentioned, several studies have found that religion does not produce negative effects on luxury consumption (Alserhan et al, ; Arli et al, ). In contrast, other studies confirmed that religion has significant effects on luxury consumption (Al‐Hyari et al, ; Burroughs & Rindfleisch, ).…”
Section: Hypothesis Developmentmentioning
confidence: 84%
“…Previous studies investigated this issue (see Bakar, Lee, & Hazarina Hashim, ; La Barbera & Gürhan, ; Pace, ), but the results were inconsistent. Recent studies found that religion does not have a negative effect on luxury consumption (Alserhan, Bataineh, Halkias, & Komodromos, ; Arli, Cherrier, & Tjiptono, ; Dekhil, Boulebech, & Bouslama, ; Teimourpour & Heidarzadeh Hanzaee, ). In contrast, prior studies found that religion has a significant effect on luxury consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Saudis are the greatest luxury admirers with social, hedonic and functional components playing a critical role in evaluating value. High levels of these factors can be explained by a general Muslim perception of consumption as a key element of identity formation (Alserhan, 2014). Buying luxury goods builds a positive social image showing a high material status (Tjahjono, 2011, Teimourpour & Hanzaee, 2014.…”
Section: E-survey Resultsmentioning
confidence: 99%
“…The fact that Arab women living in the GCC region perceived brands as less important vehicles for self-expression than women in all other countries is interesting indeed when considering how much they spend on brands and the sheer size of the market, which is expected to reach a value of nearly 2.9 billion USD in the year 2015 in the UAE alone (Euromonitor International, 2010). Moreover, and according to the same report from Euromonitor International, the GCC market is characterized as a "label me" one, where the person becomes the sum of the brands possessed (Alserhan et al, 2014).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Therefore, if respondents reported that brands are less important for self-expression, how come they spend so much to acquire them? Why do they converse so much about the brands they own and the places they acquired them from (Alserhan et al, 2014)? Did respondents report the ideal, not the factual?…”
Section: Discussion Of Resultsmentioning
confidence: 99%